Connections Between Sexuality and Disability Are Challenges for Thinking of a Diverse and Inclusive School (Interdisciplinary Studies Journal, 2021)
The aim of this article is to problematize two social markers of difference that, although recognized as promoters of diversity, cause panic for many when their presence is noticed in the classroom: issues related to sexuality and those related to disability. Thus, we work with the idea that it is not just about understanding diversity in schools as a result of the inclusion of individuals with certain social markers of difference; rather, each individual is a complex unit of various markers, which act in connection and relation to the class of students. This makes the task of building a school characterized by diversity quite complex, from both sociability and cognitive perspectives. Similarly, associated with the phenomenon of the body, in which the absence of limbs or the presence of functional limitations become defining elements of the subject, we understand that disability should be seen as just another way of living and experiencing the biological body. This means affirming that disability is an expression of human diversity, endowed with meanings that cannot be restricted to the space of discourse, where the sexuality of these individuals is subjected to the provisional nature of theoretical and legal terms, imposing upon them a normatized sexuality.
Keywords: Diversity; People with Disabilities; Sexuality, Inclusive Education.; Inclusive Education